ChemInform Abstract: Phase Diagrams of Conventional and Inverse Functional Magnetic Heusler Alloys: New Theoretical and Experimental Investigations. Issue 26 (6th June 2013) - Entel, P.; Gruner, M. E.; Hucht, A.; Dannenberg, A.; Siewert, M.; Herper, H. C.; Kakeshita, T.; Fukuda, T.; Sokolovskiy, V. V.; Buchelnikov, V. D.
Abstract Review: 88 refs.